The victim’s perspective of the interventions to address the spike in gender-based violence during the COVID-19 pandemic in Kakamega Central Sub-County, Kenya - Meli, Jacob Kipkoech; Onyango, Erick Ater; Leting, Mark; Onsarigo, Thomas Gisemba (Nairobi Journal of Humanities and Social Sciences, 2023)
The Covid-19 pandemic has led to a significant rise in gender-based violence (GBV) cases globally, necessitating targeted intervention measures. Despite efforts by governments and stakeholders, this study focuses on Kakamega Central Sub-County, Kenya, to examine whether the interventions put in place to address the GBV surge during the pandemic considered the perspectives and needs of victims. Employing the Intersectionality Theory, which explores how various forms of oppression intersect, leading to unique experiences of disadvantage, this research investigates why victims' voices may have been marginalized in intervention strategies. Using a mixed-method research design, the study involves 255 participants and 27 key informants, utilizing questionnaires, interviews, and secondary data sources. Quantitative data were analyzed using cross-tabulation and summary statistics, while qualitative data were analyzed thematically using content analysis. The reliability of the research instruments was assessed using the test-retest method, which revealed a Cronbach's alpha index of reliability exceeding 0.70 for all variables. Validity was ensured through a review of questionnaires and interview schedules to align them with the study's objectives and research variables. Findings reveal that victims perceived the interventions as inadequate and not tailored to their individual needs. Consequently, this study recommends the development of GBV intervention measures that are more responsive to the diverse and unique needs of victims, aiming to reduce GBV incidents and address root causes effectively.